Особливості акумуляції важких металів у листках деревних рослин при аерогенному забрудненні екотопів - Gryshko, V.M.; Piskova, O.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2014)
A level and rates of accumulation of Zn, Ni, Pb and Cd are determined, in the leaves of arboreal plants in the conditions of different levels of contamination. On index of intercellular contamination of leaves investigated species are subdivided into 3 groups. The species with the high level of accumulation of most heavy metals, which exceeds more than 10 times the base level (Populus bolleana Lauche, P. italica (Du Roi) Moench and Sorbus aucuparia L.) are in the first one. The second group includes plants with the average level of accumulation (exceeds the base level 5 to 10 times) — Acer negundo L. and Tilia cordata Mill. At the third group we have the species with exceeding the base level less than 5 times — Aesculus hippocastanum L., Betula pendula Roth. and Picea pungens Engelm.